The effect of ginsenosides on liver injury in preclinical studies: a systematic review and meta-analysis - Bian, Xing-Bo; Yu, Peng-Cheng; Yang, Xiao-Hang; Han, Liu; Wang, Qi-Yao; Zhang, Li; Zhang, Lian-Xue; Sun, Xin (Frontiers in Pharmacology, 2023)
Background: Liver injury is a severe liver lesion caused by various etiologies and is one of the main areas of medical research. Panax ginseng C.A. Meyer has traditionally been used as medicine to treat diseases and regulate body functions. Ginsenosides are the main active components of ginseng, and their effects on liver injury have been extensively reported. Methods: Preclinical studies meeting the inclusion criteria were retrieved from PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), and Wan Fang Data Knowledge Service Platforms. The Stata 17.0 was used to perform the meta-analysis, meta-regression, and subgroup analysis. Results: This meta-analysis included ginsenosides Rb1, Rg1, Rg3, and compound K (CK), in 43 articles. The overall results showed that multiple ginsenosides significantly reduced alanine aminotransferase (ALT) and aspartate aminotransferase (AST), affected oxidative stress-related indicators, such as superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px), and catalase (CAT), and reduced levels of inflammatory factor, such as factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6). Additionally,, there was a large amount of heterogeneity in the meta-analysis results. Our predefined subgroup analysis shows that the animal species, the type of liver injury model, the duration of treatment, and the administration route may be the sources of some of the heterogeneity. Conclusion: In a word, ginsenosides have good efficacy against liver injury, and their potential mechanisms of action target antioxidant, anti-inflammatory and apoptotic-related pathways. However, the overall methodological quality of our current included studies was low, and more high-quality studies are needed to confirm their effects and mechanisms further.